The Coverage of HIV/AIDS information in Tanzania: A Reflection of Mwananchi and Daily News Newspapers - Kanyika, Martin E.; Elia, Emmanuel F. (University of Dar es Salaam Library Journal, 2021)
The study examined the coverage of HIV/AIDS information in Tanzania ' s newspapers between 2002-2004 and 2017-2019. Two leading broadsheets that were being published on daily basis, the Daily News and Mwananchi were selected. Bibliometric and content analysis were methods used in data collection and analysis. Microsoft Office Excel 2010 was used to analyse quantitative data. Findings indicate that a total of 696 HIV/AIDS articles were covered by the two newspapers. The study also revealed an irregular coverage pattern and generally a decrease in HIV/AIDS information coverage. Findings also show HIV/AIDS themes related to politics, education on disease transmission, prevention and treatment were highly covered. In addition, HIV/AIDS international information was highly covered compared to local information. The study also observed that Daily News had better coverage of HIV/AIDS information compared to Mwananchi. The study concludes that overall the attention given to HIV/AIDS in the two newspapers was very low and fluctuated over time. The study suggests that media houses train journalists on investigative journalism practices to enhance timely, quality and increased coverage of HIV/AIDS information.